Psychological factors selectively upregulate rectal pain perception in hypersensitive patients with irritable bowel syndrome. Issue 12 (14th October 2015) - Grinsvall, C.; Törnblom, H.; Tack, J.; Van Oudenhove, L.; Simrén, M.
Abstract: Background: Visceral hypersensitivity and psychological symptoms are frequent features in irritable bowel syndrome (IBS). Exploring mechanistic pathways leading to visceral hypersensitivity is of importance to direct future studies and treatment options. In this study, we evaluated the contribution of psychological factors to the perception of painful and non‐painful rectal sensations in hyper‐ vs normosensitive IBS patients. Methods: We included 138 IBS patients (Rome II criteria) who underwent an ascending method of limited rectal balloon distension paradigm. At the end of each distension step, subjects rated the perceived intensity of non‐painful ('unpleasantness') and painful rectal sensations on visual analog scales. Sensitivity status was determined based on pain thresholds. Anxiety, depression and somatization were assessed by questionnaires. Mixed models were used to test the relationship between sensitivity status, psychological variables, and pain & unpleasantness ratings upon increasing distension. Key Results: Hypersensitive IBS patients had lower sensory thresholds for pain, first perception, urge to defecate, and discomfort ( p < 0.0001). Upon increasing distension, they rated both painful and non‐painful sensations as more intense than normosensitive patients ( p < 0.0001). Psychological factors were associated with higher pain ratings during distension in hypersensitive ( p < 0.006–0.0001), but not in normosensitive patients. Anxiety, but not depression or somatization, was associated with increased intensity ratings of non‐painful sensations ( p < 0.001), independent of sensitivity status. Conclusions & Inferences: Hypersensitive IBS patients are characterized by increased perception of pain, but also of non‐painful sensations. Psychological factors increase the perception of painful sensations in hypersensitive patients only, whereas non‐painful visceral sensations were exaggerated in anxious patients regardless of the sensitivity status. Abstract : Psychological distress is associated with increased rectal pain perception in hypersensitive, but not normosensitive, IBS patients. Anxiety, but not depression or somatization, is associated with augmented perception of non‐painful rectal sensations in all IBS patients.